Status Keuangan Negara Pada Badan Usaha Milik Negara Pasca Undang-Undang Nomor 1 Tahun 2025 - Muhlisin; Puput Shoyyibah Fatimah (Jurnal Ilmiah Kutei, 2025)
The amendment to the State-Owned Enterprises (SOE) Law introduces a new paradigm regarding the financial status of SOEs. As a result, this change creates a normative misalignment with the concept of state finances, particularly in determining state losses related to acts of corruption. This study analyzes how Law Number 1 of 2025, the Third Amendment to Law Number 19 of 2003 on State-Owned Enterprises, regulates the status of state finances within SOEs and the liability of directors for state losses. The research adopts a normative legal method, guided by legal principles, norms, rules found in legislation, court decisions, agreements, and legal doctrines. The study finds that the state's capital invested in SOEs is now considered the responsibility of the enterprise itself and is no longer regarded as state property. Following the amendment, SOEs are classified as private legal entities; however, they still retain a public dimension in terms of financial accountability due to their management of public assets. Although SOE directors are protected by the Business Judgment Rule, losses resulting from unlawful acts are still considered state losses and are subject to the public law regime governing state financial accountability.